Fatti e misfatti su un manoscritto dei Trionfi (New York, Morgan Library, ms. M. 427) - Guerrini Ferri, Gemma (Scrineum, 2013)
This article, concerning ms. M.427 of the Morgan Library of New York, intends to clear up the reasons why many people, in the past and today, think it is a fake. The origin of this mistake’s is its 1904 facsimile, but it is not diffucult to show that the auctors of this facsimile are guilty of having made a dubious publishing operation, rather than a fake.